Health Expenditures in Poland and Other European Union Countries in Years 2007–2011 - Wasiak, Anna; Szeląg, Paulina (Journal of Finance and Financial Law, 2015)
The purpose of this article is to show the size of the expenditures on healthcare in Poland in comparison to other European Union countries. The public financing is based on expenditures of National Health Fund (NFZ) and state budget expenditures, whereas in private financing expenditures on private insurance, private insurance of employers and household expenses could be pointed out. The analysis of expenditures revealed main problems in healthcare financing and proposed changes which could affect the improvement of healthcare system, both in Poland and the European Union.